2016
DOI: 10.14257/ijunesst.2016.9.7.05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Store Atmosphere on Impulse Buying Behaviour: Moderating Effect of Demographic Variables

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 51 publications
5
57
1
9
Order By: Relevance
“…The Babin and Kim (2001), studies defined that the systematic and appealing arrangement of supplies in the store other than lighting and colors dominantly affects the shopping behavior of the shoppers. Akram, Hui, Khan, Hashim, and Rasheed (2016) investigated the impact of store environment on impulse buying behavior, and concluded the result that reveals that store environment has dominant and positive effect on impulse buying behavior.…”
Section: Store Environmentmentioning
confidence: 99%
“…The Babin and Kim (2001), studies defined that the systematic and appealing arrangement of supplies in the store other than lighting and colors dominantly affects the shopping behavior of the shoppers. Akram, Hui, Khan, Hashim, and Rasheed (2016) investigated the impact of store environment on impulse buying behavior, and concluded the result that reveals that store environment has dominant and positive effect on impulse buying behavior.…”
Section: Store Environmentmentioning
confidence: 99%
“…Немонетарное регулирование может осу ще ствлять ся и через рекламные акции, которые включают в себя визуальный мерчендайзинг внутри магазина, бесплатные образцы, купоны, скидки и даже ароматы, атмосферу, фоновую музыку [Rajagopal, 2009;Tendai, Crispen, 2009;Akram et al, 2016]. Очевидно, что правительство не само применяет эти инструменты влияния на потребительский выбор, но может устанавливать некоторые регламенты, например, при использовании визуального мерчендайзинга -ограничивать размещение вредных для здоровья продуктов питания и напитков рядом с полезными.…”
Section: исследования немонетарного регулированияunclassified
“…External Factors: From the literature, in-store atmosphere (Vishnu & Raheem, 2013;Hussain & Ali, 2015;Nishanov & Ahunjonov, 2016, Akram et al, 2016, in-store browsing (Vänniä, 2013;Kim, 2003;Sangalang et al, 2017), in-store layout (Shivangunde et al, 2012;Bitner, 1992;Ohta and Higuchi, 2013;Levy & Weitz, 2011), salespersons (Evans et al, 2008;Shojaei et al, 2014;Ahuja, 2015), sales promotion ( (Jamal & Lodhi, 2015;Lin, 2013) and reference groups (Mothapo, 2013;Kumar, 2007;Tinne, 2011;Gandhi et al, 2014) where identified as essential external factors influencing consumers cognitive response to purchasing on impulse. Dynamics within the stores presentation (for example, noise, the backdrop, fittings, odour, the level of atmosphere and lights) is referred to as in-store atmosphere.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These dynamics within the store influence the response of consumers for in-store and future store decisions (Vishnu & Raheem, 2013). Music is an important variable which induces the consumer's mood, takes place at a subliminal level and creates a positive impact on impulse buying (Akram et al, 2016). According to the findings of Mattila and Wirtz (2001), good background music entices consumers to stay in the store longer to browse.…”
Section: Literature Reviewmentioning
confidence: 99%